Exploring the Internet with Netscape Communicator 4 - Grauer, Robert T. (Prentice Hall, 1998)
This book helps develop the necessary skill set to use the Internet effectively with Netscape Communicator. Concepts are presented in non-technical terms with step-by-step instructions and numerous screen captures so readers can understand and use Netscape quickly and easily. This book provides “how and why”— hands-on experience in addition to the rationale behind what is being done.